2019
DOI: 10.1021/acsami.9b20275
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Active Sites in MOF-Derived Homobimetallic Hollow Nanocages as a High-Performance Multifunctional Nanozyme Catalyst for Biosensing and Organic Pollutant Degradation

Abstract: Nanozymes are one of the ideal alternatives to natural enzymes for various applications. The rational design of nanozymes with improved catalytic activity stimulates increasing attention to address the low activity of current nanozymes. Here, we reported a general strategy to fabricate the Co-based homobimetallic hollow nanocages (HNCs) (C−CoM−HNC, M = Ni, Mn, Cu, and Zn) by ion-assistant solvothermal reaction and subsequent low-temperature calcination from metal−organic frameworks. The C−CoM−HNCs are featured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(52 citation statements)
references
References 60 publications
(109 reference statements)
0
48
0
Order By: Relevance
“…Bimetallic MOF-derived porous catalysts have also been developed for a variety of oxidation reactions, such as the oxidation of alcohols, 271,276,277 acetone, olen and toluene, 278 and organic pollutant degradation. 279,280 As an example, Han, Yeung and co-workers prepared a binary metal oxide (CeCuO x ) derived from bimetallic MOFs (CeCuBDC) as the catalyst for the oxidation of organic compounds. 278 In the oxidation of toluene to CO 2 , CeCuO x exhibited high catalytic activity, with a T 50 (temperature required for 50% conversion) and T 90 of 150 and 186 C, respectively (Fig.…”
Section: Catalysismentioning
confidence: 99%
“…Bimetallic MOF-derived porous catalysts have also been developed for a variety of oxidation reactions, such as the oxidation of alcohols, 271,276,277 acetone, olen and toluene, 278 and organic pollutant degradation. 279,280 As an example, Han, Yeung and co-workers prepared a binary metal oxide (CeCuO x ) derived from bimetallic MOFs (CeCuBDC) as the catalyst for the oxidation of organic compounds. 278 In the oxidation of toluene to CO 2 , CeCuO x exhibited high catalytic activity, with a T 50 (temperature required for 50% conversion) and T 90 of 150 and 186 C, respectively (Fig.…”
Section: Catalysismentioning
confidence: 99%
“…Among these materials, Co 3 O 4 @Co−Fe oxide DSNCs are employed for dye degradation via peroxymonosulfate (PMS) activation where the very less concentration of dye has been degraded with a comparatively higher dose of catalyst. However, CoSe 2 MS substrate affinity is inferior to Cobalt‐ZIF template‐assisted synthesized bimetallic C−CoCu hollow nanocage [57] reported for PMS activated dye degradation. In another case, CoFe 2 O 4 fails to achieve time economy even with a higher catalyst dose.…”
Section: Resultsmentioning
confidence: 90%
“…[127] Fabricating MOFs with better thermal and chemical stabilities can help provide better binding sites for pesticides. [222,223] A Zn(II)-MOF designed using an (E)-1,2-diphenyl-1,2-bis(4-(pyridin-4-yl)phenyl)ethane linker resulted in sensitive DCN sensing with quenching of the emission (quantum efficiency, 98%). In mechanistic studies, quenching was observed to occur due to binding of the MOF with pesticide DCN through H-bonding interactions (N-H … O) between the analyte amino group and MOF oxygen atom (Figure 5b).…”
Section: Mofs Sensing Behavior Toward Pesticidesmentioning
confidence: 99%